Tirucallane-Type Triterpenoids from the Dysoxylum gaudichaudianum Stem Bark: Phytochemical Study and Cytotoxicity Evaluation Against Human HeLa Cervical Cancer Cells - Maira, Faizah; Naini, Al Arofatus; Mayanti, Tri; Fajriah, Sofa; Kusumiyati, Kusumiyati; Supratman, Unang (Indonesian Journal of Chemistry, 2025)
A total of three tirucallane-type triterpenoids were successfully isolated from the n-hexane extract of the stem bark of Dysoxylum gaudichaudianum: 4,4,14-trimethyl-3-oxo-24-nor-5α,13α,14β,17α,20S-chol-7-en-23-oic (1), toonapubesin B (2), and 3β,22S-dihydroxy-tirucalla-7,24-dien-23-one (3). These compounds were isolated from D. gaudichaudianum for the first time. Structural characterization of the isolated compounds was accomplished through a series of spectroscopic analyses, including HR-TOF-MS, IR, and NMR. Based on previous reports, compound 1 was isolated from a member of the Meliaceae family for the first time. The cytotoxic properties of the isolated tirucallane-type triterpenoids were evaluated against cervical HeLa cancer cells. Among them, compounds 1 and 3 were inactive, with IC50 values > 100 µM, while compound 2 exhibited the highest cytotoxicity, with an IC50 value of 29.23 µM, with moderate activity. A structure–activity relationship also indicated the variation in cytotoxicity attributed to substituent effects within the molecular structures. The modification of the side chain in tirucallane-type triterpenoids was shown to be essential for their cytotoxic activity against human cervical cancer lines.